1994
DOI: 10.1111/j.1469-8137.1994.tb03984.x
|View full text |Cite
|
Sign up to set email alerts
|

Radial fibres in aggregate rays ofQuercus calliprinosWebb. – evidence for radial signal flow

Abstract: S U M M A R YRadial fibres differentiate in many aggregate rays of Quercus calliprinos Webb. The occurrence of radial fibres in rays suggests a radial flow of developmental stimuli for fibre differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The formation of fibers in the xylem rays of Quercus calliprinos is correlated with the radial signal flow operating in the regulation of rays (Lev-Yadun, 1994). Lev-Yadun and Aloni (1995) concluded that the formation of several radial ray centers within large vascular rays (polycentric aggregate rays) of Suaeda monoica reflects the establishment of several independent preferable pathways of radial signal flow within rays.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The formation of fibers in the xylem rays of Quercus calliprinos is correlated with the radial signal flow operating in the regulation of rays (Lev-Yadun, 1994). Lev-Yadun and Aloni (1995) concluded that the formation of several radial ray centers within large vascular rays (polycentric aggregate rays) of Suaeda monoica reflects the establishment of several independent preferable pathways of radial signal flow within rays.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of vascular elements (tracheids and vessels) in the radial direction in rays of mature wood of many species (Vliet, 1976;Botosso and Vidal Gomes, 1982;Carlquist, 1988;Fahn, 1990) further indicates that part of the radial signal flow is auxin and that its concentration is high enough to induce sieve or tracheary elements in the radial direction (Lev-Yadun and Aloni, 1995). In the present study, it appears that formation of the radial sieve elements in the rays of secondary phloem may also be associated with the radial signal flow (Lev-Yadun, 1994;Lev-Yadun andAloni, 1991, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The radial system (the vascular rays) is usually composed of parenchyma, although other cell types such as tracheids, resin and gum ducts, radial phloem, and radial fibers may infrequently be found in the rays (Fahn, 1990;Aloni, 1991a, 1995;Lev-Yadun, 1994b). Like the types of ring porosity mentioned above, the specific structure of the rays-(1) height in cell number, (2) width in cell number, (3) having radial resin or gum ducts, (4) having cells of only the same size and if not, their size variation, 5having radial components such as tracheids, fibers, and phloem, and being of two size categories (huge and small) as in oaks-is used for identification (e.g., Greguss, 1955;Fahn et al, 1986;IAWA, 1989IAWA, , 2004Schweingruber, 1990).…”
Section: The Anatomical Basis For Wood Identification Basic Types Of mentioning
confidence: 99%